Chronic low-grade inflammation and ovarian dysfunction in women with polycystic ovarian syndrome, endometriosis, and aging - Orisaka, Makoto; Mizutani, Tetsuya; Miyazaki, Yumiko; Shirafuji, Aya; Tamamura, Chiyo; Fujita, Masayuki; Tsuyoshi, Hideaki; Yoshida, Yoshio (Frontiers in Endocrinology, 2023)
The ovarian microenvironment is critical for follicular development and oocyte maturation. Maternal conditions, including polycystic ovary syndrome (PCOS), endometriosis, and aging, may compromise the ovarian microenvironment, follicular development, and oocyte quality. Chronic lowgrade inflammation can induce oxidative stress and tissue fibrosis in the ovary. In PCOS, endometriosis, and aging, pro-inflammatory cytokine levels are often elevated in follicular fluids. In women with obesity and PCOS, hyperandrogenemia and insulin resistance induce ovarian chronic low-grade inflammation, thereby disrupting follicular development by increasing oxidative stress. In endometriosis, ovarian endometrioma-derived iron overload can induce chronic inflammation and oxidative stress, leading to ovarian ferroptosis and fibrosis. In inflammatory aging (inflammaging), senescent cells may secrete senescence-associated secretory phenotype factors, causing chronic inflammation and oxidative stress in the ovary. Therefore, controlling chronic low-grade inflammation and fibrosis in the ovary would present a novel therapeutic strategy for improving the follicular microenvironment and minimizing ovarian dysfunction.